Quantifying Cooperation Benefits for New Dams in Transboundary Water Systems Without Formal Operating Rules - Gonzalez, Jose M.; Matrosov, Evgenii S.; Obuobie, Emmanuel; Mul, Marloes; Pettinotti, Laetitia; Gebrechorkos, Solomon H.; Sheffield, Justin; Bottacin-Busolin, Andrea; Dalton, James; Smith, D. Mark; Harou, Julien J. (Frontiers in Environmental Science, 2021)
New dams impact downstream ecosystems and water infrastructure; without cooperative and adaptive management, negative impacts can manifest. In large complex transboundary river basins without well codified operating rules and extensive historical data, it can be hard to assess the benefits of cooperating, in particular relating to new dams. This constitutes a barrier to harmonious development of river basins and could contribute to water conflict. This study proposes a generalised framework to assess the benefits of cooperation on the management of new dams in water resource systems that do not have formal sharing arrangements. Benefits are estimated via a multi-criteria benefit comparison of carrying on with historical reservoir operations (usually relatively uncooperative) vs. adopting new cooperative rules which would achieve the best achievable results for riparians. The approach is applied to the Pwalugu Multipurpose Dam (PMD), which is being implemented in Ghana’s Volta river basin. The Pwalugu dam could impact ecosystems and downstream infrastructure in Ghana and could itself be impacted by how the existing upstream Bagre dam is managed in Burkina Faso. Results show that with cooperation Ghana and Burkina Faso could both increase energy production although some ecosystem services loss would need to be mitigated. The study confirms that cooperation achieves higher overall/basin wide benefits compared to seeking benefits only for individual dams or countries.